Outcomes of Children With Bronchiolitis Treated With High-Flow Nasal Cannula or Noninvasive Positive Pressure Ventilation*. Issue 2 (February 2019) - Clayton, Jason A.; McKee, Bryan; Slain, Katherine N.; Rotta, Alexandre T.; Shein, Steven L.
Abstract : Objectives: Initial respiratory support with noninvasive positive pressure ventilation or high-flow nasal cannula may prevent the need for invasive mechanical ventilation in PICU patients with bronchiolitis. However, it is not clear whether the initial choice of respiratory support modality influences the need for subsequent invasive mechanical ventilation. The purpose of this study is to compare the rate of subsequent invasive mechanical ventilation after initial support with noninvasive positive pressure ventilation or high-flow nasal cannula in children with bronchiolitis. Design: Analysis of the Virtual Pediatric Systems database. Setting: Ninety-two participating PICUs. Patients: Children less than 2 years old admitted to a participating PICU between 2009 and 2015 with a diagnosis of bronchiolitis who were prescribed high-flow nasal cannula or noninvasive positive pressure ventilation as the initial respiratory treatment modality. Interventions: None. Subsequent receipt of invasive mechanical ventilation was the primary outcome. Measurements and Main Results: We identified 6, 496 subjects with a median age 3.9 months (1.7–9.5 mo). Most (59.7%) were male, and 23.4% had an identified comorbidity. After initial support with noninvasive positive pressure ventilation or high-flow nasal cannula, 12.3% of patients subsequently received invasive mechanical ventilation. Invasive mechanical ventilation was more common in patients initially supported with noninvasive positive pressure ventilation compared with high-flow nasal cannula (20.1% vs 11.0%: p < 0.001). In a multivariate logistic regression model that adjusted for age, weight, race, viral etiology, presence of a comorbid diagnosis, and Pediatric Index of Mortality score, initial support with noninvasive positive pressure ventilation was associated with a higher odds of subsequent invasive mechanical ventilation compared with high-flow nasal cannula (odds ratio, 1.53; 95% CI, 1.24–1.88). Conclusions: In this large, multicenter database study of infants with acute bronchiolitis that received initial respiratory support with high-flow nasal cannula or noninvasive positive pressure ventilation, noninvasive positive pressure ventilation use was associated with higher rates of invasive mechanical ventilation, even after adjusting for demographics, comorbid condition, and severity of illness. A large, prospective, multicenter trial is needed to confirm these findings. Abstract : Supplemental Digital Content is available in the text.